Phylogenetic relationships of the subfamily Pyrgulinae (Gastropoda: Caenogastropoda: Hydrobiidae) with emphasis on the genus Dianella Gude, 1913 - Szarowska, Magdalena; Falniowski, Andrzej; Riedel, Frank; Wilke, Thomas (Zootaxa, 2005)
The phylogenetic position of the subfamily Pyrgulinae within the superfamily Rissooidea has been discussed very controversially. Different data sets not only led to different evolutionary scenarios but also to different systematic classifications of the taxon. The present study uses detailed anatomical data for two pyrgulinid taxa, the type species of the subfamily, Pyrgula annulata (Linnaeus, 1767), and the type species of the little known genus Dianella, D. thiesseana (Kobelt, 1878), as well as DNA sequencing data of three gene fragments from representatives of eight rissooidean families to A) infer the phylogenetic position of Pyrgulinae with emphasis on its relationships within the family Hydrobiidae, B) to study the degree of concordance between anatomyand DNAbased phylogenies and C) to trace the evolution of anatomical characters along a multi-gene molecular phylogeny to find the anatomical characters that might be informative for future cladistic analyses. Both anatomical and molecular data sets indicate either a very close or even sister-group relationship of Pyrgulinae and Hydrobiinae. However, there are major conflicts between the two data sets on and above the family level. Notably, Hydrobiidae is not monophyletic in the anatomical analysis. The reconstruction of anatomical character evolution indicates that many of the characters on which the European hydrobioid taxonomy is primarily based upon are problematic. The inability to clearly separate some hydrobiids from other distinct families based on those characters might explain why until only a few years ago, "Hydrobiidae" was a collecting box for numerous rissooidean taxa (mostly species with shells small and lacking any characteristic features). The present study not only stresses the need for comprehensive molecular studies of rissooidean taxa, it also demonstrates that much of the problems surrounding anatomical analyses in rissooidean taxa are due to the lack of comprehensive data for many representatives. In order to aid future comparativeanatomical studies and a better understanding of character evolution in the species-rich family Hydrobiidae, detailed anatomical descriptions for P. annulata and D. thiesseana are provided.Key words: Pyrgulinae, Pyrgula, Dianella, Hydrobiidae, phylogeny, DNA, anatomy, Greece